2022
DOI: 10.5223/pghn.2022.25.3.276
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and Associated Factors of Infantile Colic in Thai Infants

Abstract: Purpose Infantile colic, a common functional gastrointestinal condition, causes distress and frustration in families. Its prevalence and incidence vary from community to community. The purpose of our study was to demonstrate the incidence of and factors associated with infantile colic in Thai infants. Methods We conducted a prospective analytic study to explore the incidence and factors associated with infantile colic in 386 Thai infants aged between one month and six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…Although there is limited supporting evidence, previous studies have suggested that low-income mothers with less social support tend to have difficulty feeding their premature infant, possibly resulting in increased infant colic [17,39]. However, in two other studies, a protective effect of EBF on infant colic was reported within the first 2 months of life [11,40]. In other words, EBF can be associated with reduced infant colic.…”
Section: Discussionmentioning
confidence: 96%
“…Although there is limited supporting evidence, previous studies have suggested that low-income mothers with less social support tend to have difficulty feeding their premature infant, possibly resulting in increased infant colic [17,39]. However, in two other studies, a protective effect of EBF on infant colic was reported within the first 2 months of life [11,40]. In other words, EBF can be associated with reduced infant colic.…”
Section: Discussionmentioning
confidence: 96%
“…The HMOs metabolism by Bifidobacteria produces metabolites with potential host‐health effects, including alleviating pain associated with functional gastrointestinal disorders, such as infantile colic 39 . A study conducted in Thailand in 2022 also demonstrated that infants exclusively breastfed for the first 2 months had a significantly lower incidence of infantile colic compared to those who received mixed feeding or formula feeding (Odds Ratio = 3.0; 95% confidence intervals = 1.3–7.2) 40 . The study suggests that breastfeeding may act as a protective factor against infantile colic.…”
Section: Discussionmentioning
confidence: 99%
“…39 A study conducted in Thailand in 2022 also demonstrated that infants exclusively breastfed for the first 2 months had a significantly lower incidence of infantile colic compared to those who received mixed feeding or formula feeding (Odds Ratio = 3.0; 95% confidence intervals = 1.3-7.2). 40 The study suggests that breastfeeding may act as a protective factor against infantile colic.…”
Section: Lactobacillus Reuterimentioning
confidence: 95%
“…18 Nuestro factor protector para presentar CI fue la convivencia con los padres. Suklert y col. 8 encontraron en lactantes de Thailandia que aquellos que fueron amamantados exclusivamente durante los primeros 2 meses de vida tuvieron una menor incidencia de CI que los que recibieron alimentación mixta o con fórmula (OR = 3,0; IC95% = 1,3 a 7,2; p < 0,05). Nuestros factores de riesgo para presentar CI incluyeron ser asistido por un gastroenterólogo pediatra, de institución privada, tener un TECI en un familiar que conviva con el lactante y ser de raza mestiza.…”
Section: Discussionunclassified
“…Los criterios de Roma IV definen cólico infantil (CI) como el lactante menor de 5 meses de edad, sano, que presenta períodos recurrentes y prolongados de llanto, molestia e irritabilidad que ocurren sin una causa obvia y no pueden ser prevenidos o resueltos por sus cuidadores. 1 Su prevalencia está entre 1,9% y 19,2%, [2][3][4][5][6][7] relatándose como factores de riesgo: lactantes con alimentación mixta o con fórmula, 8 madre migrañosa 9 y con mayor nivel educativo, ser recién nacido con bajo peso al nacer 6 y haber nacido prematuramente. 10,11 Sin embargo, en Latinoamérica no han sido reportados ni su prevalencia ni los factores de riesgo.…”
unclassified